2015
DOI: 10.1097/dss.0000000000000360
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Radiofrequency and Intralesional Steroids in the Treatment of Keloids

Abstract: Radiofrequency tissue volume reduction combined with IL steroid is an effective treatment modality for keloids. It is an easy procedure with acceptable cosmetic outcome and less rate of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
0
13
0
3
Order By: Relevance
“…Fruth et al treated auricular keloids with RF ablation (1-7 treatments), half in combination with intralesional administration of triamcinolone, and saw improvement in 6/7 treated with combination therapy and 4/7 with RF ablation monotherapy [48]. A subsequent study saw improvement in 12 out of 13 lesions (92.3%), with only one patient requiring multiple treatments; the authors acknowledged that there was no explanation for the divergence between their results and those of Fruth et al [49] Further evaluation of combination therapy with RF ablation and steroid injection was found to decrease keloid volume (95.4% reduction), pain, and pruritus [50]. Support of these results was found in a comparison of triamcinolone, triamcinolone and hyaluronidase, verapamil, RF, and RF with triamcinolone.…”
Section: Radiofrequency (Rf) Ablationmentioning
confidence: 97%
“…Fruth et al treated auricular keloids with RF ablation (1-7 treatments), half in combination with intralesional administration of triamcinolone, and saw improvement in 6/7 treated with combination therapy and 4/7 with RF ablation monotherapy [48]. A subsequent study saw improvement in 12 out of 13 lesions (92.3%), with only one patient requiring multiple treatments; the authors acknowledged that there was no explanation for the divergence between their results and those of Fruth et al [49] Further evaluation of combination therapy with RF ablation and steroid injection was found to decrease keloid volume (95.4% reduction), pain, and pruritus [50]. Support of these results was found in a comparison of triamcinolone, triamcinolone and hyaluronidase, verapamil, RF, and RF with triamcinolone.…”
Section: Radiofrequency (Rf) Ablationmentioning
confidence: 97%
“…Similarly, studies with RF showed be er result when adjunc ve ILCS was used. 38 Three studies on RF reviewed here, all of which showed good result with no recurrence except one study where a small scar recurred in 10% of cases at fi ve year follow up. 15,37,38 However, none of the other studies did this long dura on follow up of fi ve years.…”
Section: Discussionmentioning
confidence: 73%
“…38 Three studies on RF reviewed here, all of which showed good result with no recurrence except one study where a small scar recurred in 10% of cases at fi ve year follow up. 15,37,38 However, none of the other studies did this long dura on follow up of fi ve years. Both the studies on PDT reviewed here used MAL as a photosensi zing agent and irradiated the lesions using a red light with a wave length of 630 nm and light dosage at 37 J/ cm2.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, no statistically significant differences were found between the results for atrophic and hypertrophic scars, respectively. In the treatment of hypertrophic scars, some authors have reported good results with injected triamcinolone, [11][12][13] whereas atrophic scars appear to improve with the application of iontophoresis with retinoic acid (tretinoin). [14][15][16] In a previous study of atrophic and hypertrophic acne scars, we obtained attenuations of almost 60% by transepidermal delivery of cosmeceuticals with bioactive components and whitening substances (allantoin, bisabolol, sodium hyaluronate, glycosaminoglycans, dipotassium glycyrrhizate, vitamin B complex, vitamin C, and low molecular weight peptides).…”
Section: Discussionmentioning
confidence: 99%